The internal loads, moments, and stresses in rod-like particles in a low-speed, vertical axis mixer. (29th September 2015) - Hua, X.; Curtis, J.; Guo, Y.; Hancock, B.; Ketterhagen, W.; Wassgren, C.
Abstract: A discrete element method (DEM) model is used to predict the internal load and moment distribution within rod-like particles in a low-speed, vertical axis mixer. The internal loads and moments are combined with small deformation beam bending theory to determine the internal stress distributions. Parametric studies using the model examined the influence of particle aspect ratio, blade rotational speed, and material properties. The spatial distributions of loads and moments, averaged over all particles and time steps, are symmetric about the particle center-plane with a maximum at the particle center-plane. In addition, the largest average maximum absolute principal stress is observed to occur along the particle circumference at the center-plane of the particle. These results indicate that particle failure is not only most likely to occur at the center-plane of the particle, but the failure will begin at the particle's circumference. The largest average loads, moments, and maximum absolute principal stress increase with particle aspect ratio. The frequency distributions of maximum absolute principal stress at the high stress range are fit well with a Weibull distribution. Increasing blade speed, bed height and particle–particle friction coefficient generally lead to an increase in internal loads, moments, and stresses. The largest maximum absolute principal stresses occur at the base of the mixer and in front of the blades near the mixer circumference where the bed depth is the greatest. Highlights: New model for predicting internal loads, moments and stresses in rod-like particles. Predictions made for varying particle properties and process conditions in a mixer. Maximum absolute principal stresses fit well with a Weibull distribution. Largest stresses occur at particle center-plane and circumference on average. Stresses increase with aspect ratio and fill; friction and speed not as important.